Surfing equipment and design: a scoping review - Romanin, A.; English, S.; Furness, J.; Kemp-Smith, K.; Newcomer, S.; Nessler, J. (Sports Engineering, 2021)
Growth in the surfing equipment industry has led to increased scientific interest in this area, yet no current paper has reviewed and synthesized the effects of equipment design on surfing. Therefore, the aims of this study were to: (1) assess the volume and type of scientific literature that is available to the authors specific to surfing equipment and design, (2) summarise all surfing equipment and design studies completed to date specific to outcome measures and key findings and (3) identify knowledge gaps in the topic of surfing equipment design. This review was conducted in accordance with the PRISMA scoping review guidelines. A total of seven electronic databases were searched (PubMed, Embase, CINAHL, SPORTDiscus, Web of Science, SCOPUS, and Ovid). Google Scholar was also searched for grey literature. Inclusion criteria were mention of surfing equipment and relevant surfing outcome measures (physiological and mechanical). Exclusion criteria were no full text availability and works not available in English. Results from these articles were then extracted, summarised and presented. A total of 17 articles were selected for review and organized by theme of board, wetsuit and fin. Fin and wetsuit design were the most prominent themes (seven studies each respectively). Most were written within the past 5 years and written in the USA. Fin design studies were largely computational, whereas board and wetsuit design were mostly field and laboratory based. Within each study theme there were consistencies in outcome measures and measuring devices. Board design studies focused on paddling efficiency (VO2 and HR). Wetsuit design studies primarily assessed thermoregulation, and less so muscle activation and paddling biomechanics. Fin design studies focused on fin shape and configuration to assess lift and drag properties. Three key themes of board, wetsuit and fin design were noted; from this the authors were able to identify several knowledge gaps such as a lack of standardisation in equipment controls and study design procedures. Alongside improving standardisation, the use of wave pools presents as an area of interest in future research.